Desempenho e características quantitativas da carcaça de borregos Morada Nova, submetidos a restrição de nutrientes em dietas de terminação - Luz, Abdias Nascimento (2019)
The aim of the present study was to evaluate the effects of diets formulated according to the National Research Council - NRC (2007), with or without nutrient restriction, on Morada Nova lambs, with early maturity being predicted. Thus, the effects of dietary nutritional levels on the consumption, performance, morphometric measurements and carcass characteristics of Morada Nova sheep in the termination stage were evaluated. The experiment was carried out as a completely randomized design comprising two diets (100 and 85% of the NDT and PB requirements, as stipulated by the NRC (2007) - D100 and D85, respectively) for lambs in the termination stage with average gain of 200 g day-1, resulting in two treatments comprising 14 replicates, totaling 28 experimental animals. The feed was pelleted and supplied ad libitum. The lambs had a mean age of 161 days of age, weighed on average 19.04 ± 2.94 kg and were slaughtered with an average weight of 28.69 ± 4.04 kg. The confinement period consisted in 64 days. Performance parameters (final body weight, daily average weight gain, body condition score, dry matter intake, feed conversion, feed efficiency and residual food consumption), morphometric parameters (wither height, anterior depth, height of the anterior leg, thoracic perimeter, body length, croup height, posterior leg height, posterior depth, femur length and leg perimeter), as well as carcass evaluations (fasting body weight, empty body weight, warm carcass weight, cold carcass weight, warm carcass yield, cold carcass yield, biological carcass yield, loin eye area, fat thickness and cooling cracking index) and non-carcass components were assessed. The F-test was used at 5% of probability for a variance analysis and comparison of means. No effects (P> 0.05) of D100 and D85 on the consumption, performance and carcass evaluation parameters in Morada Nova lambs were observed, evidencing the efficiency of these animals at lower nutrient intakes. In addition, non-carcass components did not differ (P> 0.05) between diets, except for the liver and pancreas (% PCVZ) (P <0.05), higher in D85, suggesting a metabolic overload in these organs. Concerning efficiency, the adoption of a diet formulated with 85% of the requirements prescribed by the NRC (2007) for Morada Nova lambs in the termination stage is recommended.